Generation of hyaline-like cartilage tissue from human mesenchymal stromal cells within the self-generated extracellular matrix. (1st September 2022) - Xie, Mingsheng; Zhang, Yiqian; Xiong, Zixuan; Hines, Sophie; Shang, Jiangyinzi; Clark, Karen L.; Tan, Susheng; Alexander, Peter G.; Lin, Hang
Abstract: Chondrocytic hypertrophy, a phenotype not observed in healthy hyaline cartilage, is often concomitant with the chondrogenesis of human mesenchymal stromal cells (hMSCs). This undesired feature represents one of the major obstacles in applying hMSCs for hyaline cartilage repair. Previously, we developed a method to induce hMSC chondrogenesis within self-generated extracellular matrix (mECM), which formed a cartilage tissue with a lower hypertrophy level than conventional hMSC pellets. In this study, we aimed to test the utility of hypoxia and insulin-like growth factor-1 (IGF1) on further reducing hypertrophy. MSC-mECM constructs were first subjected to chondrogenic culture in normoxic or hypoxic (5%) conditions. The results indicated that hMSC-derived cartilage formed in hypoxic culture displayed a significantly reduced hypertrophy level than normoxic culture. However, hMSC chondrogenesis was also suppressed under hypoxic culture, partially due to the reduced activity of the IGF1 pathway. IGF1 was then supplemented in the chondrogenic medium, which promoted remarkable hMSC chondrogenesis under hypoxic culture. Interestingly, the IGF1-enhanced hMSC chondrogenesis, under hypoxic culture, was not at the expense of promoting significantly increased hypertrophy. Lastly, the cartilage tissues created by hMSCs with different conditions were implanted into osteochondral defect in rats. The results indicated that the tissue formed under hypoxic condition and induced with IGF1-supplemented chondrogenic medium displayed the best reparative results with minimal hypertrophy level. Our results demonstrate a new method to generate hyaline cartilage-like tissue from hMSCs without using exogenous scaffolds, which further pave the road for the clinical application of hMSC-based cartilage tissue engineering. Statement of significance: In this study, hyaline cartilage-like tissues were generated from human mesenchymal stromal cells (hMSCs), which displayed robust capacity in repairing the osteochondral defect in rats. In particular, the extracellular matrix created by hMSCs was used, so no exogenous scaffold was needed. Through a series of optimization, we defined that hypoxic culture and supplementation of insulin-like growth factor-1 (IGF-1) in chondrogenic medium resulted in robust cartilage formation with minimal hypertrophy. We also demonstrated that hypoxic culture suppressed chondrogenesis and hypertrophy through modulating the Wnt/β-catenin and IGF1 pathways, respectively. Our results demonstrate a new method to generate hyaline cartilage-like tissue from hMSCs without using exogenous scaffolds, which will further pave the road for the clinical application of hMSCs-based cartilage tissue engineering. Graphical abstract: Image, graphical abstract